Pengaruh Leverage, Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan Periode Tahun 2015- 2017 - Kurniawan Kurniawan; Suharto Mulyanta (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
This research aims to review the influence of leverage that is measured using a debt to equity ratio (DER), profitability is measured using return on assets (ROA) and return on equity (ROE) and liquidity as measured by using current ratio on the value the company which is measured using price to book value (PBV in the mining sector companies that listed on Indonesia stock exchange (BEI) in period 2015-2017. This kind of research is the study of causal samples with a purposive sampling technique. The result of this research is expected provide contribution, reference, information and empirical evidence required to parties who needs regarding leverage, profitability, liquidity and its relation to the value of enterprise.